Analysis of article 518 LEC, expiration and prescription of the action in the execution. Reference to the doctrine of the unfair delay in the exercise of the right (Acta Judicial Journal, 2020)
This article aims to present in a practical and simple way, a study about the legal institutions of the expiration and the prescription of the action in the execution process, with reference to the doctrine of unfair delays in the exercise of the right.
Keywords: Expiration, 518, Prescription, 1964, Instance, Execution, Unfair Delay